PERFIL DOS ACIDENTES DE TRABALHO NO SETOR FLORESTAL NO ESTADO DO ESPÍRITO SANTO, BRASIL - Santos, Vinicius Pereira dos (2020)
The objective of the present work was to get to know the profile of occupational accidents in the forestry sector in the state of Espírito Santo, Brazil, proposing a methodology for analyzing occupational accidents in planted forests, native forests and a